Preparation and characterization of electrospun PLGA/gelatin nanofibers as a potential drug delivery system - Meng, Z.; Xu, X.; Zheng, W.; Zhou, H.; Li, L.; Zheng, Y.; Lou, Xia (Elsevier BV, 2011)
Drug (Fenbufen, FBF)-loaded poly(D,L-lactide-co-glycolide) (PLGA) and PLGA/gelatin nanofibrous scaffolds were fabricated via electrospinning technique. The influences of gelatin content, fiber arrangement, crosslinking time and pH value of the buffer solution on FBF release behavior of the resulting nanofibrous scaffolds were investigated, with the corresponding FBF-loaded PLGA and PLGA/gelatin solvent-cast films as controls. The release rate of FBF was found to be increased with the increment of gelatin content for all the composite samples, and the FBF release rate of aligned nanofibrous scaffold was lower than that of randomly oriented scaffold. Moreover, the crosslinking treatment depressed effectively the burst release of FBF at initial release stage of PLGA/gelatin (9/1) nanofibrous scaffold. In addition, the pH value of the buffer solution could change the physical state of the polymer and affect the FBF release rate.